Detrital-zircon geochronology of the eastern Magallanes foreland basin: Implications for Eocene kinematics of the northern Scotia Arc and Drake Passage - Barbeau, David; Olivero, Eduardo Bernardo; Swanson Hysell, Nicholas L.; Zahid, Khandaker M.; Murray, Kendra E.; Gehrels, George E. (Earth and Planetary Science Letters)
U/Pb detrital-zircon geochronology of eleven sandstones collected from Cretaceous through Oligocene strata of the eastern Magallanes foreland basin of southernmost Argentina records a dramatic provenance shift near the end of the middle Eocene at ca. 39 Ma. From the Late Cretaceous through most of the middle Eocene, detrital zircons reaching the foreland basin were dominantly contributed from ≤ 140 Ma sources, most likely derived from the Patagonian-Fuegian magmatic arc. In contrast, detrital-zircon populations of sampled upper Eocene and Oligocene strata are dominated by 150-190 Ma and pre-Mesozoic grains presumably derived from ignimbrites and granitoids associated with the break-up of Gondwana and from metasedimentary rocks of the Cordillera Darwin metamorphic complex, respectively. Exposures of these units occur in the hinterland of the Fuegian Andes thrust belt and inboard of the Patagonian-Fuegian batholith, suggesting that middle to late Eocene shortening in the rear of the Fuegian orogenic wedge structurally dammed batholith-derived sediment from reaching the foreland basin while contributing Jurassic and pre-Mesozoic detritus from hinterland thrust sheets. The timing of this interpreted deformation is in agreement with (1) independent structural, stratigraphic, and thermochronometric evidence of middle Paleogene deformation in the Fuegian Andes, and (2) marine Nd isotope ratio data that reveal initial penetration of Pacific water through the Drake Passage, thereby suggesting a possible link between the kinematics of the Fuegian Andes, the opening of Drake Passage, and if related, the Oi-1 glaciation of Antarctica. Fil: Barbeau, David. University of South Carolina; Estados Unidos Fil: Olivero, Eduardo Bernardo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Swanson Hysell, Nicholas L. University of South Carolina; Estados Unidos Fil: Zahid, Khandaker M. University of South Carolina; Estados Unidos Fil: Murray, Kendra E. ...